A precarious hybridity: war, mission, nationalism, anti-nationalism and the Murray family of South Africa - Muller, Retief (Stellenbosch Theological Journal, 2022)
Since their arrival in South Africa in the early 19th century, the Murray family walked something of a tightrope with respect to the formation of Afrikaner national identity. This article describes the Murrays' positioning regarding that identity formation as a "precarious hybridity". On the one hand, the Murrays identified themselves closely with the Afrikaner people among whom they ministered, an identification that was particularly tested by the traumatic experience of the South African War (1899-1902). On the other hand, they maintained wider ecumenical and international linkages, which were particularly enhanced by their involvement in missionary activities in Nyasaland. Such variegated positioning necessitated a pragmatic, accommodationist approach that was increasingly at odds with the hardening identity formation characteristic of Afrikaner nationalism as the 20th century proceeded. This article describes and analyses the ways in which some of these complexities played out.